Relationship between emotional intelligence and learning motivation among college students during the COVID-19 pandemic: A serial mediation model - Tang, Yuxi; He, Weiguang (Frontiers in Psychology, 2023)
The vital influence of emotional intelligence on college students’ learning motivation has received considerable attention. This study analyzed not only the relationship between emotional intelligence and college students’ learning motivation during the COVID-19 pandemic, but also the serial mediating roles that self-efficacy and social support play in this relationship. Using a cross-sectional survey design, we collected data from 336 college students across 30 provinces in China, using four well-established scales measuring emotional intelligence, learning motivation, self-efficacy, and social support. We analyzed the mediating effects using the Bootstrap method. The results showed that emotional intelligence positively predicted learning motivation, and that self-efficacy and social support played serial mediating roles between emotional intelligence and learning motivation. This finding suggests the need for interventions to help college students develop emotional intelligence during the COVID-19 pandemic, and that fostering college students’ self-efficacy and providing multiple social supports would help improve their motivation and academic performance